Tracking the untraceable - An assessment of global obliteeration techniques on small arms - Henwood, Bailey J. (Cranfield University, 2023)
The illicit trafficking and proliferation of small arms and light weapons is of international concern to organisations such as the United Nations, state governments, and non-government organisations. Violent extremist groups and organised criminal groups alike sanitise weapons to conceal their identity and undermine forensic tracing operations. These groups demonstrate sufficient forensic awareness to know that serial numbers and other identifying marks are used to track firearms throughout their lifecycles, across porous borders, and through criminal networks, exposing illicit actors to risk of prosecution. Weapon sanitisation remains an area of concern across the globe, with little transnational monitoring of obliteration methodology undertaken. This thesis investigates marks that have been intentionally obliterated from firearms to render untraceable weapons trackable through illicit facilitation routes. To enable field-based forensic recovery of removed markings, this research explores an emerging magneto-optical technology. A methodology for utilising this kit has been established within this thesis, with the recovery of obliterated markings surpassing the current methods that utilise a chemical etchant (Fry’s reagent) by up to 22%. This emerging technology has proven to be a beneficial forensic capability and preserves the integrity of evidence, while highlighting that some marks may never be recovered even using the most effective, current techniques. To enable the investigations of non-recoverable marks, this thesis undertakes the first known investigation into the tracking of obliterations on a global level by developing a novel, intelligence-led investigative codification tool based on the toolmark analysis of individual obliterations. This unique tool has been designed to ensure that technical analysis is not restricted by location nor forensic capability. The development and methodology of this novel framework to critically analyse the toolmarks within obliterations has been presented. This approach has been proven in this work to be a useful method to track global obliteration trends when coupled with local intelligence, showing physical links between sanitised weapons documented in Africa, the Middle East, Canada, the United Kingdom, and Australia. 125 unique clusters encompassing 81% of weapons analysed were established in this research, with 82 of these clusters crossing international and continental borders. The developed methods and techniques, conclusions, and recommendations of this research have been presented to, and adopted by, international research organisations demonstrating the impact of this novel contribution to knowledge.
Keywords: Firearm; Tool mark analysis; Sanitisation; Non-destructive recovery; Intelligence; Criminological investigation